Development of Lucilia sericata (Diptera: Calliphoridae) Under Constant Temperatures and its Significance for the Estimation of Time of Death. Issue 5 (16th March 2020) - Wang, Man; Wang, Yu; Hu, Guoliang; Wang, Yinghui; Xu, Wang; Wu, Maowang; Wang, Jiangfeng
Abstract: Forensic entomologists usually estimate the minimum postmortem interval (PMImin ) using the time required for the oldest immature insects found on the corpse to grow to its development stage and age at the time of discovery. The sheep blow fly Lucilia sericata (Meigen, 1826) is a carrion fly found nearly worldwide, and important in forensics. We studied the development time of L. sericata from egg to adult at constant temperatures of 16, 19, 22, 25, 28, 31, and 34°C, and found that the times required are 913.2 ± 19.4, 588.8 ± 35.8, 459.8 ± 15.2, 373.2 ± 15.3, 308.0 ± 9.7, 272.5 ± 9.2, and 267.5 ± 10.5 h, respectively. We established three development models to infer the age of the immature insect: isomegalen diagram, isomorphen diagram, and thermal summation model. In addition, a regression analysis was performed on the relationship between body length and total development time from hatching to dispersing. The thermal summation constant during the development of L. sericata is 6023.2 degree hours and development threshold temperature is 9.19°C. The results of this experiment provide a basis for the use of L. sericata in the estimation of PMImin .